2015
DOI: 10.3109/13880209.2014.993041
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid pretreatment mitigates MPTP-induced motor impairment and histopathological alterations in C57BL/6 mice

Abstract: This study provides elementary evidence for the neuroprotective action of FA against MPTP-induced PD in mice and warrants further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…[16]; dose-dependent amelioration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced loss of nigrostriatal dopaminergic neurons, the decrease of the Bax/Bcl2 ratio, reduction of pro-apoptotic protein Bax levels and increased expression of anti-apoptotic protein Bcl2 in PD C57BI/6 mice model (ferulic acid was given via injections for 7 days, at a dose of 20, 40 and 80 mg/kg) [17];…”
Section: Figurementioning
confidence: 99%
“…[16]; dose-dependent amelioration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced loss of nigrostriatal dopaminergic neurons, the decrease of the Bax/Bcl2 ratio, reduction of pro-apoptotic protein Bax levels and increased expression of anti-apoptotic protein Bcl2 in PD C57BI/6 mice model (ferulic acid was given via injections for 7 days, at a dose of 20, 40 and 80 mg/kg) [17];…”
Section: Figurementioning
confidence: 99%
“…Importantly, very recent studies have shown that FA attenuated neuroinflammation and improved behavioral deficits against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD. 21 , 22 MPTP is mainly used to develop PD model in mice and nonhuman primates. However, for unknown reasons, among rodents the rats are resistant, but mouse specifically C57BL/6 strain, is highly sensitive to MPTP.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Previous studies show that intraperitoneally administered MPTP (25–30 mg/kg body weight) once daily for five consecutive days leads to the development of Parkinsonism in mice. 22 , 24 Administration of these doses of MPTP for very short duration is considered as an acute model of PD. Moreover, MPTP model shows nonprogressive mode of cell death, motor impairments, and lack of intracytoplasmic inclusion of α-synuclein.…”
Section: Introductionmentioning
confidence: 99%
“…Catalepsy test is a widely used noninvasive method designed to evaluate mouse limb strength . It has also been used to investigate the effects of neuromuscular disorders .…”
Section: Discussionmentioning
confidence: 99%
“…The production of catalepsy in animals by neuroleptic drugs is adduced to the inhibition of dopaminergic function and is antagonized by dopaminergic agonists . Both clinical and experimentally induced motor side effects and catalepsies have been shown to respond to dopamine receptor agonists . In contrast, the antagonists of D2 receptors or muscarinic receptor agonists exhibit opposite effects .…”
Section: Discussionmentioning
confidence: 99%